PERKAWINAN TIDAK TERCATAT: PUDARNYA HAK-HAK PEREMPUAN (Studi di Kabupaten Cianjur) - Kustini Kustini; Nur Rofiah (Harmoni, 2013)
The purpose of the research is to understand the phenomena of the unregistered marriage, comprises the causes, effects, responses and efforts to minimize unregistered marriage. The method is qualitative method with the strategy of case study. The data collecting technique are through deep interview, focused group discussion, document examination and observation. The location of the research is Cianjur and the field data collection occurred on August 2012. Causal factors of the unregistered marriage are the lack understanding of religion, that does not require the registration, the religion figure’s influence and role, law factor, and or administration issue. The unregistered marriage has bad effects to the women, as their position as wives is legally unconsidered. Muslim’s leader and the society give various responses to the unregistered marriage, some say that the registration is not something that is eligible for Islam, while some other say that it is a positive endeavor related to its law status as well as its cause and effect. Efforts to avoid unregistered marriage have been done by the society as parents and the government collaborating with self-supporting institutions. Parents do it through education and family resuscitation while the government does it through isbat nikah and the socialization of how important the registration is.